2021
DOI: 10.1101/2021.03.24.21254271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 RT-PCR diagnostic assay sensitivity and SARS-CoV-2 transmission: A missing link?

Abstract: Background The sensitivity of commercially available RT-PCR assays varies over 10,000 fold, ranging from 10 to 20,000 viral copies/ml. The reporting of high Ct value results has been under scrutiny, as the clinical significance of these values is not yet completely understood. The early detection of infected individuals (high Ct results) in the pre-symptomatic phase of the disease using highly sensitive RT-PCR methods has been argued as a strategy to prevent transmission, while on the contrary, the reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…These data suggest that our surveillance system is likely to be sufficiently sensitive to detect all infectious SARS-CoV-2 carriers, given that an individual’s viral load beneath our limit of detection is generally thought not to be contagious, given multiple reported failures to cultivate any SARS-CoV-2 virus using in vitro cell culture from samples with Ct values of over minimum reported thresholds ranging from 24 to 33 26-28 . Indeed, sequencing of SARS-CoV-2 transcripts from infected cells recently established that full genome sequence coverage was not observed in samples with a Ct greater than 32 (measured with the same Perkin Elmer RT-PCR assay which we used here as our comparator 29 ), suggesting that any RT-PCR detection of small SARS-CoV-2 genomic fragments in samples beyond this threshold would not likely reflect intact viable virus with potential to be infectious.…”
Section: Resultsmentioning
confidence: 97%
“…These data suggest that our surveillance system is likely to be sufficiently sensitive to detect all infectious SARS-CoV-2 carriers, given that an individual’s viral load beneath our limit of detection is generally thought not to be contagious, given multiple reported failures to cultivate any SARS-CoV-2 virus using in vitro cell culture from samples with Ct values of over minimum reported thresholds ranging from 24 to 33 26-28 . Indeed, sequencing of SARS-CoV-2 transcripts from infected cells recently established that full genome sequence coverage was not observed in samples with a Ct greater than 32 (measured with the same Perkin Elmer RT-PCR assay which we used here as our comparator 29 ), suggesting that any RT-PCR detection of small SARS-CoV-2 genomic fragments in samples beyond this threshold would not likely reflect intact viable virus with potential to be infectious.…”
Section: Resultsmentioning
confidence: 97%
“…We had previously sequenced 827 samples ranging from 10 to 42 Ct values, of which 95 samples were with Ct value >37 with PE RT-PCR assay [ 10 ]. Of the 827-sample sequenced, the percentage of sequencing reads that aligned to the SARS-CoV-2 Wuhan-hu-1 reference genome (NC_045512.2) ranged from 5.1 to 100%.…”
Section: Clinical Significance Of High Ct Results Obtained With a Highly Sensitive Rt-pcr Assaymentioning
confidence: 99%
“…All samples sequenced showed high sequence specificity to the SARS-CoV-2 virus. Low-Ct samples showed complete uniform coverage across the entire 29 kb SAR-CoV-2 genome, whereas the coverage in samples with high-Ct (>37) ranged from 5.1% to 99.9%, and a gradual decrease in coverage uniformity was observed with increasing Ct values [ 10 ]. The results of our study confirmed that samples with >37 Ct value reported with PE RT-PCR assay were true positive results and not PCR artifacts or contamination.…”
Section: Clinical Significance Of High Ct Results Obtained With a Highly Sensitive Rt-pcr Assaymentioning
confidence: 99%